Dendrchoronological potential of Pinus rzedowskii Madrigal et Caballero: an endemic species of Michoacán - Manzanilla Quiñones, Ulises; Delgado-Valerio, Patricia; Carlón-Allende, Teodoro; Molina-Sánchez, Agustín (Ecosistemas y Recursos Agropecuarios, 2023)
Pinus rzedowskii is a pine species endemic to Michoacán, distributed in the Sierra de Coalcomán. The objective of this research was to analyze the dendrochronological potential of the species. Sixty-six growth cores were taken from 22 trees of P. rzedowskii. The samples were analyzed by dendrochronological techniques, the ring width was measured in a VELMEX® equipment, the quality of the dating and measurement was verified by Cofecha. A chronology was generated in Arstan, then Bootstrap correlations were performed between the chronology and climatic data from weather stations near the study site. The dated samples (n = 45, r = 0.403, p < 0.01) covered 1730-2021, indicating that the longest-lived tree is 292 years old. According to the evaluation of dendrochronological parameters; P. rzedowskii has a relatively low dendrochronological potential, however, it presents a significant climatic signal (r = 0.52, p < 0.01) with autumn-spring precipitation.
Keywords: Tree rings; radial growth; dendrochronology; Pinus; autumn-winter precipitation